The Dynamics of Indonesian CPO Price Integration with European and Indian Markets (Empirical Insights) - Mega Amelia Putri; Kumbara Kumbara; Arnayulis Arnayulis; Darnetti Darnetti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Dynamic price interconnections and external market influences characterize the global crude palm oil (CPO) market. As the world's largest producer, Indonesia faces challenges in stabilizing prices amidst regulatory pressures from European markets and the significant role of India as a key export destination. This study aims to analyze the integration and dynamics of Indonesian CPO prices with European and Indian markets using advanced econometric tools, including Vector Auto Regression (VAR) and Vector Error Correction Model (VECM). Monthly price data from January 2016 to December 2022 were sourced from reliable databases such as BAPPETI and UN Comtrade. The findings highlight significant price volatility in the Indonesian spot market (CV = 46.18%) compared to Europe (CV = 39.22%) and India (CV = 29.74%), with the latter serving as a stabilizing force. Granger causality tests reveal mutual influence between Indonesia and Europe, while India's unidirectional causality underscores its role in mitigating external shocks. Cointegration analysis confirms long-term equilibrium relationships among the markets, with European and Indian markets contributing 33.61% and 29.35%, respectively, to Indonesian price variability over 12 months. These insights emphasize the importance of establishing a domestic futures market to manage volatility and diversifying export destinations to reduce reliance on traditional markets. This study provides actionable recommendations for policymakers and stakeholders to strengthen Indonesia's resilience and competitiveness in the global CPO market.